An Ethicolegal Analysis of Involuntary Treatment for Opioid Use Disorders. Issue 4 (December 2020) - Udwadia, Farhad R.; Illes, Judy
Supply-side interventions such as prescription drug monitoring programs, "pill mill" laws, and dispensing limits have done little to quell the burgeoning opioid crisis. An increasingly popular demand-side alternative to these measures – now adopted by 38 jurisdictions in the USA and 7 provinces in Canada — is court-mandated involuntary commitment and treatment. In Massachusetts, for example, Part I, Chapter 123, Section 35 of the state's General Laws allows physicians, spouses, relatives, and police officers to petition a court to involuntarily commit and treat a person whose alcohol or drug abuse poses a likelihood of serious harm. This paper explores the ethical underpinnings of this law as a case study for others. First, we highlight the procedural and substantive standards of Section 35 and evaluate the application of the law in practice, including the frequency with which it has been invoked and outcomes. We then use this background to inform an ethical critique of the law. Specifically, we argue that the infringement of autonomy and privacy associated with involuntary intervention under Section 35 is not currently justified on the grounds of a lack of evidenced benefits and a risk of significant of harm. Further ethical concerns also arise from a lack of standard of care provided under the Section 35 pathway. Based on this analysis, we advance four recommendations for change to mitigate these ethical shortcomings.